Combined effect of different factors on weight status and cardiometabolic risk in Italian adolescents - Antonino Bianco; Anna Rita Filippi; João Breda; Vincenza Leonardi; Antonio Paoli; Luca Petrigna; Antonio Palma; Garden Tabacchi (BMC, 2019)
Abstract Background The observed increase in body weight and cardiometabolic risk (CR) in youth from developed countries contributes to the global burden of chronic diseases in adult age. The aim of this work is to provide a patterning of the associations between different factors and the weight status and CR of the subjects involved in the Italian ministerial ASSO project. Methods This study involved 919 students from high schools in Palermo. Weight, height and waist circumference were collected by trained teachers; weight status was estimated by the BMI cut-offs for adolescents and CR through the waist-to-height ratio. Questionnaires were administered through the web-based ASSO-NutFit software. Chi-square test investigated the variables significantly associated with the outcomes, which were then included in a Multiple Correspondence Analysis (MCA), to explore their dimensional relationship to weight status and CR. Poisson regressions were conducted separately for the two outcomes, reporting raw and adjusted prevalence ratios (PRs) and Bootstrap Method was used to determine confidence intervals (CIs), to assessing the degree of effect of the explanatory variables over the outcomes. Results Two main dimensions were evidenced, with the overweight/obese group and the group at CR characterized by the following strongly associated factors: male gender, overweight/obese parents, following a slimming regime, caesarean birth, sedentariness, being under/overweight at birth, presence of metabolic risk, going to school by car/scooter, not using supplements. Conclusions This study contributed to identifying those adolescents that should be prioritized in interventions aiming at reducing overweight/obesity and CR in this age group.